CSA options implemented and Evaluated across the CCAFS Climate-Smart Villages AR4D sites: 2016 Global Inventory - Bonilla Findji, Osana; Tan Yen, Bui; Khatri-Chhetri, Arun; Kimeli, Philip; Leguía Hidalgo, Efraín José; Martínez Barón, Deissy; Ouédraogo, Mathieu; Radeny, Maren A.O.; Recha, John W.M. (2017)
Location of the Climate-Smart Villages AR4D sites across the five focal CCAFS regions.